2017
DOI: 10.1111/ajpy.12148
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mindfulness meditation training on executive functions and emotion dysregulation in an Iranian sample of female adolescents with elevated attention‐deficit/hyperactivity disorder symptoms

Abstract: Background: Mindfulness-based interventions improve a variety of clinical outcomes. Executive functioning (EF) and emotion dysregulation are among the proposed transdiagnostic mechanisms that such interventions are proposed to target. The aim of the current study was to evaluate the impact of mindfulness meditation training on EF and emotion dysregulation in a sample of female adolescents with elevations in attention-deficit/hyperactivity disorder (ADHD) symptoms against a waitlist control condition. Method: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 39 publications
(47 reference statements)
4
49
0
Order By: Relevance
“…Specific components of the speed-accuracy tradeoff in regard to cognitive control performance might have been differentially responsive to specific aspects of yoga training within this young adult sample. Yoga training is commonly imparted as a combination of postures and breath exercises and occasionally is combined with other activities such as listening to music, chanting, deity worship, experience-sharing, and motivational speeches (e.g., Manjunath and Telles, 2001;Levine et al, 2011;Kiani et al, 2016). Each of these activities could differentially influence executive control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific components of the speed-accuracy tradeoff in regard to cognitive control performance might have been differentially responsive to specific aspects of yoga training within this young adult sample. Yoga training is commonly imparted as a combination of postures and breath exercises and occasionally is combined with other activities such as listening to music, chanting, deity worship, experience-sharing, and motivational speeches (e.g., Manjunath and Telles, 2001;Levine et al, 2011;Kiani et al, 2016). Each of these activities could differentially influence executive control.…”
Section: Resultsmentioning
confidence: 99%
“…Further, regulation of the speed-accuracy tradeoff within the three components of executive control might be the unifying mechanism through which yoga training is influential. Studies examining the effect of mindfulness-related practice on cognitive task performance report either speed (RT) or accuracy, but not both, as in the case with working memory tasks (e.g., Jella and Shannahoff-Khalsa, 1993;Jyothsna and Rao, 2014;Sharma et al, 2014;Johnson et al, 2015;Jansen et al, 2017;Purohit and Pradhan, 2017;Crivelli et al, 2018), planning and cognitive flexibility (e.g., Levine et al, 2011;Kiani et al, 2016), and inhibitory control (e.g., Lakey et al, 2007;Semple, 2010;Alfonso et al, 2011;Moore et al, 2012;Kiani et al, 2016;Wimmer et al, 2016). Results suggest that analyzing speedaccuracy tradeoff might be useful in exploring the unifying mechanism by which yoga and other mindfulness practices might enhance executive control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, more rigorous RCTs have produced conflicting evidence, with benefits on the Stroop task observed in some RCTs, but not others. Those that noted improved post-training performance in the mindfulness, but not the comparison group, demonstrated evidence of faster reaction time (RT; Bhayee et al, 2016;Fan et al, 2014;Malinowski et al, 2017) and lower accuracy and RT interference (Allen et al, 2012;Fan et al, 2014;Johns et al, 2016;Kiani, Hadianfard, & Mitchell, 2016). One particularly welldesigned RCT examined affective Stroop interference in participants completing a 6-week mindfulness intervention compared with participants engaged in a group-based reading and listening group that was carefully designed to match the training group for non-specific factors (Allen et al, 2012).…”
Section: Mindfulness Training and Measures Of Top-down Attentionmentioning
confidence: 99%
“…Compared to a Fatigue Education and Support Group, 8-week Mindfulness Based Stress Reduction (MBSR) training yielded greater improvements in Stroop accuracy interference, and these gains were maintained at a 6-month follow-up. Importantly, these RCTs (with the exception of Kiani et al, 2016) limited the influence of non-specific factors by comparing mindfulness training to active control groups that included psychoeducation and support (Johns et al, 2016), reading groups (Allen et al, 2012), brain training (Malinowski et al, 2017), math training (Bhayee et al, 2016), and progressive muscle relaxation (Fan et al, 2014). Thus, these studies provide confidence that the observed gains in Stroop performance can indeed be attributable to engagement with mindfulness practices rather than non-specific factors including social support, engagement with stimulating materials, or facilitation of an intervention by experts.…”
Section: Mindfulness Training and Measures Of Top-down Attentionmentioning
confidence: 99%